Potency Of Andrographolide, L-Mimosine And Asiaticoside Compound As Antiviral For Covid-19 Based On In Silico Method - Ningrum, Dhecella; Aini, Dita; Juniananda, Melisa; Febriansah, Rifki (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Introduction - COVID-19 is an infectious disease that is a global challenge, making it necessary for innovation and the development of antiviral agents in prevention and treatment efforts. Indonesia is known as a country rich in potential plants as medicine, a potential antiviral plant among them Andrographis paniculata , Mimosa pudica and Centella asiatica. The compound that have antiviral activity in each of these plants are andrographolide (Andrographis paniculata), L-mimosine (Mimosa pudica) and asiaticoside (Centella asiatica). The purpose of this study is to identify the potential of the andrographolide, l-mimosine and asiaticoside to inhibit SARS COV-2 protein and to predict the molecular drug profile which refers to lipinski's rule of 5. Purpose - The purpose of this study was to determine the potential of Andrographis paniculata , Mimosa pudica and Centella asiatica compounds in inhibiting the SARS CoV-2 protein and to determine the prediction of drug profiles such as molecules referring to Lipinski's rule of 5. Methodology - The methods used in this research by molecular docking and lipinski's Ro5 using PKCSM. The control compounds used are favipiravir and remdesivir. Results - The results of the affinity of target protein bonds using molecular docking obtained the best results in NSP3 proteins with An Asiaticoside docking score of -10.1 kcal / mol stronger than favipiravir -5.3 kcal/mol and remdesivir -8.6 kcal/mol. As for the compounds L-mimosine -6.1 kcal / mol and Andrographolide -7.7 kcal / mol. The compounds of andrographolide and L-mimosine showed good results and met the 5 aspects of Lipinski's Ro5, but asiaticoside compounds did not good enough. . Conclusion - The Research has concluded that the compound of the Andrographis paniculata , Mimosa pudica and Centella asiatica have a good potential in inhibiting SARS cov2 protein that is stronger than favipiravir and almost the same with remdesivir activity.